PENGARUH RASIO KEUANGAN DAN PENURUNAN TARIF PAJAK TERHADAP PEMBAYARAN DIVIDEN - Ayem, Sri; Fatimah, Andinie (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
The aim of this study is to find out whether financial ratios and decreases in tax rates affect the payment of dividends in goods and consumption industry sector companies that are listed on the Indonesia Stock Exchange. This study uses secondary data with the documentation method in the form of the company's annual financial statements. The research period was conducted from 2012 – 2016. The research approach used is a quantitative approach with purposive sampling sampling method. Of the 40 population companies of goods and consumption industry sectors listed on the Indonesia Stock Exchange a sample of 12 companies was taken with a period of 5 years. Dividend payments are proxied using the Dividend Payout Ratio. The profitability level is proxied by using earnings per share and return on assets, and the level of liquidity is calculated using the current ratio. The results of this study state that a decrease in tax rates affect the dividend payout ratio, and the return on asset, current ratio and earning per share have no effect on dividend payout ratio.Keywords: Return on Asset, Current Ratio, Earning per Share, Decrease In Tax Rates and Dividend Payout Ratio